2010
DOI: 10.2131/jts.35.709
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing effects of carbon tetrachloride on in vivo mutagenicity in the liver of mice fed 2-amino-3,8-dimethylimidazo[4,5-f]quinoxaline (MeIQx)

Abstract: -Chronic stimulus subsequent to cell injury plays an important role in cancer development, but the precise mechanisms remain unknown partly because appropriate animal models are lacking. In the present study, the effects of hepatotoxicant carbon tetrachloride (CCl 4 ) on in vivo mutagenicity were investigated using gpt delta mice with or without p53. Female B6C3F 1 p53-proficient or -deficient gpt delta mice were given a diet containing 300 ppm of 2-amino-3,8-dimethylimidazo[4,5-f]quinoxaline (MeIQx) for 13 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The total RNA from the cerebellum samples was isolated using the Isogen kit (Nippon gene, Tokyo, Japan) according to the manufacturer's protocol (Okamura et al, 2010). The first strand of cDNA was synthesized using the PrimeScript TM RT reagent kit (Takara, Shiga, Japan).…”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%
“…The total RNA from the cerebellum samples was isolated using the Isogen kit (Nippon gene, Tokyo, Japan) according to the manufacturer's protocol (Okamura et al, 2010). The first strand of cDNA was synthesized using the PrimeScript TM RT reagent kit (Takara, Shiga, Japan).…”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%
“…CCl 4 treatments enhanced MF even in the p53-deficient background. [ 138 ] 9-(4′-aminophenyl)-9 H -pyrido[3,4- b ]indole (aminophenylnorharman, APNH) C57 BL6/J mice male diet for 12 weeks gpt and Spi − liver 10 ppm + G:C to T:A transversions, followed by G:C to A:T transitions, were the most frequent mutations detected by gpt assay. Single G deletions in run sequences were detected by Spi − selection.…”
Section: Introductionmentioning
confidence: 99%
“…Such assays are promising tools for investigating the relationship between chemical genotoxicity and carcinogenicity. As additional analyses, various factors related to chemical carcinogenesis, such as DNA modifications, oxidative stress, cell proliferation and metabolic enzyme activities can also be measured in transgenic rodents [4][5][6][7][8][9][10][11] . This review focuses on reported renal carcinogens found in natural products such as d-limonene and aristolochic acid (AA), food additives such as potassium bromate (KBrO 3 ) and madder color (MC), and mycotoxins such as ochratoxin A (OTA) and citrinin (CTN).…”
Section: Introductionmentioning
confidence: 99%